Karakterisasi Fungi Basidiomycota di Areal Kampus Institut Pertanian Bogor - Kurniawati Purwaka Putri; Sedek Karepesina; Amandita Lintang Rumondang; Ivan Permana Putra (Universitas Bengkulu, 2023)
Bogor Agricultural University (IPB University) is one of the campuses in Indonesia that still has large green open spaces with various tree vegetation. These environmental conditions strongly support the growth of macrofungi. The diversity of macrofungi at IPB University has been previously reported. However, most of the existing reports are not equipped with microscopic identification characteristics. This study aims to explore the diversity of Basidiomycota in the IPB University and to characterize the mushroom fruiting bodies macroscopically and microscopically. The method used is foraging which is then followed by identification based on macroscopic and microscopic characteristics. The results of this study confirmed that the Basidiomycota found included Psathyrella sp., Phallus indusiatus, and Coprinellus section Disseminati. The current work adds data on the diversity of fungi in the IPB University campus area as one of the green campuses in Indonesia. Regular monitoring efforts still need to be carried out in various other areas within the IPB University campus.